Keterampilan Mengajar Mahasiswa Calon Guru Dalam Melaksanakan Program Seminar Praktik Sekolah (SPS) di SMAN 1 Kota Tambolaka - etheldreda rosari garung (Faktor Jurnal Ilmiah Kependidikan, 2022)
This study aims to describe the skills of colleger in implementing the School Practice Seminar Program (SPS).  The method used in this research is descriptive qualitative involving 7 students of the Physics Education study program at SMAN 1 Kota Tambolaka.  Data collection techniques use method of observation and documentation.  The research instrument is the rubric assessing for teaching skills of the colleger.  Data analysis techniques are  the form of presenting data and drawing conclusions from results  of the research. The observed teaching skills consist of eleven components.  The results showed that the average skill in opening learning was 3.8, the skill in applying the steps of learning was 3.6, the skill in using learning methods was 3.3, the skill in using learning media was 3.4, the skill in using language was 3,  4, material mastery is 2.7, class mastery is 3.2, time management is 3.3, participation is 3.7, interaction is 3.8 and learning closing skills is 3.7.  Overall, the teaching skills of colleger are in the very good category.